Drug Dosing in Renal Disease - Doogue, Matthew P (The Australian Association of Clinical Biochemists, 2011)
Renal disease alters the effects of many drugs, particularly when active drug moieties are renally cleared. Drug doses should usually be reduced in renal disease in proportion to the predicted reduction in clearance of the active drug moiety. Patient factors to consider in adjusting drug doses include the degree of renal impairment and patient size. Drug factors to consider in adjusting doses include the fraction of the drug excreted unchanged in urine and the drug’s therapeutic index. Estimates of renal function are useful to guide dosing of renally cleared drugs with medium therapeutic indices, but are not precise enough to guide dosing of drugs with narrow therapeutic indices. This article discusses principles of drug dose adjustment in renal disease.